Karakteristik Teh Jelai (Coix Lacryma-Jobi.L) dengan Perlakuan Waktu dan Suhu Roasting yang Berbeda - Siti Masithah Fiqtinovri; Nurlina; Sri Rahayu (Universitas Djuanda, 2024)
Jelai (Coix Lacryma Jobi.L) seeds are grains that have the potential to be processed into herbal teas which are served either hot or cold. Jelai tea can be processed through a high-temperature roasting process to enhance the aroma and taste. Temperature and length of roasting time are factors that affect grain characteristics. The purpose of this study was to evaluate the effect of temperature and roasting time on water content, color of barley powder and the effect of temperature and roasting time on pH, total dissolved solids, and organoleptic of jelai tea. The study used a factorial completely randomized design (CRD) with two factors: (t) roasting temperature (180oC, 200oC, 220oC) and (f) roasting time (5 minutes, 10 minutes, 15 minutes). The roasting temperature and time reduced the water content of jelai powder from 11.04% to 1.57% (wb), increased the dissolved solids from 0.26 oBrix to 5.16 oBrix, and lowered the pH from 7.04-6.79. The higher the temperature and roasting time, the darker the color of the powder and the barley tea (brown), increase the burning aroma (burn aroma), nutty smelling, burn flavor and the sour taste of jelai tea. The highest results were obtained at 220oC combined roasting time of 10 minutes and 15 minutes. Overall, the level of panelist acceptance of jelai tea was in the rather favorable category for all treatments (2.77 – 3.42).